Identificação e mapeamento de marcador RAPD associado ao gene Co-13 de resistência à antracnose do feijoeiro comum - Lacanallo, Giselly Figueiredo (2008)
The cultivar Jalo Listras Pretas (JLP) is an important source of resistance to anthracnose, disease of great occurrence in common bean (Phaseolus vulgaris L.) caused by the fungus Colletotrichum lindemuthianum. This common bean cultivar presents the Co-13, one of the three Andean resistant genes currently identified. In this study, the F2 population derived from the crossing between JLP (resistant to race 73) and Cornell 49-242 (susceptible to race 73) were evaluated. Bulked Segregant Analysis was utilized to identify Random Amplified Polymorphic DNA (RAPD) markers linked the gene Co-13 present in JLP. Within the RAPD primers utilized, the OPV20680 (5'CAGCATGGTC3') amplified a heteromorphic band in 680 pb, at coupling phase, linked to the Andean resistant gene Co-13. The F2 population genotyping with the OPV20680 marker showed a recombination frequency of 1.72%. The use of this marker in the segregation analysis of resistence in the population of the recombinant endogamic lines (RIL's) fitted a ratio of 1:1. These results showed that the marker OPV20680 is linked to the resistant gene Co-13 at a distance of 1.8 cM, mapped on B3 linkage group of the consensus map of common bean Jalo EEP558 x BAT 393. Thus, the use of molecular markers linked to Andean resistant genes consists in a valuable source to obtain cultivars with wide and durable resistance spectrum, therefore, assisting common bean breeding programs.